Effects of alkali-metal ions on phospholipid and triglyceride synthesis in rat liver slices - R.S. Leal (Journal of Lipid Research, 1965)
The influence of alkali-metal ions on the incorporation of labeled precursors into phospholipids and triglycerides was studied in rat liver slices. By use of acetate-1-C14 and palmitate-1-C14 as lipid precursors, a comparison was made of the pathway from acetate to phospholipid and the pathway from palmitate to phospholipid. While the rate of incorporation of palmitate-1-C14 into phospholipids and triglyceride fatty acids was virtually independent of the alkali-metal ion present in the medium, the rate of incorporation of acetate-1-C14 into the same compounds was strongly influenced by the alkali-metal ions, the highest incorporations being obtained with potassium and rubidium. Under the same conditions lithium appears to have an inhibitory effect. The effects of the alkali-metal ions on phospholipid and triglyceride synthesis in liver are located on the pathway between acetate and long-chain fatty acids.